1989
DOI: 10.1007/bf00124314
|View full text |Cite
|
Sign up to set email alerts
|

Budget deficits and interest rates in the United States

Abstract: During the last several years, the issue of the effect of budget deficits on interest rates in the United States has attracted considerable attention. However, not only has the issue remained unsettled, but more recently has become even more clouded by conflicting evidence. For example, Cebula (1987) reported a significant and positive effect on ex post short-term real interest rate, Kolluri and Giannaros (1987) a significant and negative effect on ex-ante short-term real rate, Makin (1983) a 'mixed to weak' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
2
8
0
2
Order By: Relevance
“…Feldstein [1], Hoelscher [2], Wachtel and Young [3], Zahid [4], Thomas and Abderrezak [5], Miller and Russek [6], Raynold [7], Cebula [8], Vamvoukas [9], Ewing and Yanochik [10], and Saleh and Harvie [11] maintained that there is a positive relationship between the government deficit/debt and the interest rate. However, Kormendi [12], Hoelscher [13], Aschauer [14], Makin [15], McMillin [16], Evans [17][18][19], Gupta [20], Darrat [21,22], Findlay [23], and Ostrosky [24] indicated that more government deficit/debt would not lead to a higher interest rate. Barro [25][26][27] argued that more government deficit/debt would not increase aggregate demand because people would save more in order to pay more future tax to pay off government debt.…”
Section: Literature Surveymentioning
confidence: 99%
“…Feldstein [1], Hoelscher [2], Wachtel and Young [3], Zahid [4], Thomas and Abderrezak [5], Miller and Russek [6], Raynold [7], Cebula [8], Vamvoukas [9], Ewing and Yanochik [10], and Saleh and Harvie [11] maintained that there is a positive relationship between the government deficit/debt and the interest rate. However, Kormendi [12], Hoelscher [13], Aschauer [14], Makin [15], McMillin [16], Evans [17][18][19], Gupta [20], Darrat [21,22], Findlay [23], and Ostrosky [24] indicated that more government deficit/debt would not lead to a higher interest rate. Barro [25][26][27] argued that more government deficit/debt would not increase aggregate demand because people would save more in order to pay more future tax to pay off government debt.…”
Section: Literature Surveymentioning
confidence: 99%
“…The task of establishing such a relationship is ambiguous and might be the reason that thwarts the analysis of this link prior to the deregulation of interest rates. However, contrary to the popular belief that an administered interest rate in developing countries is insensitive to market perceptions, the literature revealed that an administered interest rate does accommodate market signals, and in order to analyze that, the literature has suggested examining the intertemporal movement of the interest rate and its variability (Gupta 1984).…”
mentioning
confidence: 90%
“…Feldstein [15], Hoelscher [20], Cebula [7], Cebula and Cuellar [10], Cebula [8,9], Cebula, Angjellari-Dajci, and Foley [11] and others indicate that more government deficit/debt raises real interest rates and is likely to crowd out spending by households and businesses. On the other hand, McMillin [24], Gupta [17], Darrat [12,13], Findlay [16], Ostrosky [26] and others maintain that more government deficit/debt would not raise the interest rate. Tables 1 and 2 report the basic statistical analysis and the simple correlation between real GDP and the right-hand side variables.…”
Section: The Modelmentioning
confidence: 99%